Development and performance evaluation of a banana chipper - FELIX JOHN RAJASREE MADHAVAN; Er. Prince M. V (Tavanur 1997 Department of Post Harvest Technology & Agricultural Processing)
to develop a mechanical banana chipper, evaluate the performance of the machine and compare with manual chipping
Development and performance evaluation of a banana chipper